Reconstrução de contornos e cumeeiras de telhados de edifícios a partir de imagens aéreas de alta-resolução e poliedros representativos de edifícios extraídos de dados LASER - Marcato, Vanessa Jordão [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
This paper proposes improvements in a previous methodology for the geometric refinement of building roof contours extracted from LASER data using high-resolution aerial images and Markov Random Field (MRF) models. The original methodology takes for granted that the 3D description of each building roof reconstructed from the laser scanning data is topologically correct and that it is only necessary to improve its accuracy. Since roof ridges are accurately extracted from laser scanning data, our main objective is to use high-resolution aerial images to improve the accuracy of roof outlines. For this, this methodology uses lines extracted form the image and the projection of the roof contours extracted from the LASER data to establish a MRF description based on relations of length, proximity and orientation between the two sets of straight lines. One of the proposed improvements is to include in the energy function associated with the MRF a restriction called corner injuction. This restriction considers that the intersection of two adjacent lines, corresponding to the contour sides, should be close to a corner in 90º. The corners are extracted from an image through an appropriate image processing algorithm. Other improvement in the energy function is based on the fact that the lines representing roof contours are aproximately parallel or orthogonal. This restriction was called rectangularity injuction. Other modification in the original methodology refers to the energy function optimization algorithm. The original methodology used the brute force optimization algorithm associated with some heuristics. Although this method allows to obtain the optimal solution, if there is, the search space becomes computationally intractable when dozens of lines are in the search space. It is proposed to use a genetic algorithm in order to solve this problem...

Esse trabalho propõe melhorias em uma metodologia preexistente para o refinamento geométrico de contornos de telhados extraídos de dados LASER, usando imagens aéreas de alta resolução e campos aleatórios de Markov (MRF - Markov Random Field). A metodologia original assume que a descrição 3D de cada telhado de edifício reconstruído de dados de varredura a LASER está topologicamente correta e que é necessário apenas melhorar sua acurácia. Uma vez que as cumeeiras de telhado são acuradamente extraídas de dados de varredura a LASER, o objetivo básico é usar imagens aéreas de alta resolução para melhorar somente a qualidade geométrica dos contornos de telhado. Para tanto, essa metodologia utiliza retas extraídas da imagem e as projeções dos contornos de telhados extraídos dos dados LASER para estabelecer uma descrição MRF com base em relações de comprimento, proximidade e orientação entre ambos os conjuntos de retas. A função de energia associada com a descrição MRF é minimizada através de uma versão modificada do algoritmo de força bruta, resultando em um agrupamento de retas para cada contorno de telhado. Uma das melhorias propostas nesse trabalho consiste em incluir na função de energia associada ao MRF uma restrição denominada injunção de quina. Esta restrição leva em conta que a intersecção de duas retas adjacentes, correspondentes a lados de contorno, deve estar próxima de uma quina em 90º. As quinas são extraídas na imagem através de um algoritmo apropriado de processamento de imagem. Outra melhoria na função de energia baseia-se no fato de que as retas representativas de contornos de telhados são aproximadamente paralelas ou ortogonais entre si...
Keywords: Cartografia; Fotogrametria; Imagens digitais; Cartography